Geometric Optimization of Tubular Adhesive Joints by Cohesive Models - Rosas, M. F. M. O.; Campilho, R. D. S. G.; Moreira, R. D. F. (Technological Innovation in Engineering Research Vol. 4, 2022)
Tubular adhesive joints are used in the construction, motorsport, and piping industries, despite the fact that they are rarely examined. This work numerically analysed, by finite elements (FE) combined with cohesive zone modelling (CZM), the tensile performance of aluminium tubular joints bonded with the adhesive Araldite® 2015, considering geometric changes that potentially promote a strength improvement. Tubular joints present larger bonded areas and higher flexural strength owing to their overall stiffness. Axisymmetric CZM modeling for this purpose was validated prior to the numerical investigation by comparing experimental data. An outer chamfer, an inner chamfer (both in the adherends), and an adhesive fillet at the overlap ends were the geometric alterations investigated in this study. Due to adherend plasticization, the studied geometric alterations exhibited significant stress reductions but no noteworthy maximum load (Pm) variations.